Management Accounting Systems and Organizational Performance of Nepalese Commercial Banks - Gnawali, Achyut (Journal of Nepalese Business Studies, 2018)
Management accounting information plays a vital role in these basic management activities but most particularly in planning, decision making, costing and control functions. The purpose of this study was to examine the effect of management accounting systems on organizational performance in Nepalese commercial banks. Descriptive and casual research design has been adopted. Questionnaires and published documents are used to collect the data. It was found that management accounting systems have affected the performance of sample organizations. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page : 8-18